2004
DOI: 10.1002/app.20167
|View full text |Cite
|
Sign up to set email alerts
|

Friction and wear studies on nylon‐6/SiO2 nanocomposites

Abstract: ABSTRACT:Composites of nanometer-sized silica (SiO 2 ) filler incorporated in nylon-6 polymer were prepared by compression molding. Their friction and wear properties were investigated on a pin on disk tribometer by running a flat pin of steel against a composite disc. The morphologies of the composites as well as of the wear track were observed by scanning electron microscopy (SEM). The addition of 2 wt % SiO 2 resulted in a friction reduction () from 0.5 to 0.18 when compared with neat nylon-6. This low sili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 21 publications
1
17
0
1
Order By: Relevance
“…The peak of Si 2p in PI/SiO 2 nanocomposite is 102.68 eV at the 9 wt % nano‐SiO 2 content. This confirmed that the silica are present at (or near) the surface of the nanocomposite particles 15. In fact, the binding energy between 103.1 and 102.7 eV was assigned to the SiO bond under a different environment.…”
Section: Resultssupporting
confidence: 62%
“…The peak of Si 2p in PI/SiO 2 nanocomposite is 102.68 eV at the 9 wt % nano‐SiO 2 content. This confirmed that the silica are present at (or near) the surface of the nanocomposite particles 15. In fact, the binding energy between 103.1 and 102.7 eV was assigned to the SiO bond under a different environment.…”
Section: Resultssupporting
confidence: 62%
“…Interests in such polymer nanocomposites have been spurred on by their excellent mechanical properties like stiffness and strength with only a few percent of the nano-fillers arising from the large surface area to volume ratio when compared to the micro-fillers [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Other superior properties include abrasive wear resistance [19,20], creep and fatigue performance [21,22], heat distortion temperature [23] and permeability resistance [24][25][26]. These improved mechanical and physical properties would make polymer nanocomposites a class of superior materials for applications in automotives, adhesives, packages, microelectronics, sporting goods, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In the automotive, plastics, paper, and flooring industries, SiNPs and other inorganic materials have been incorporated into polymeric coatings to enhance their resistance to chemical and mechanical damages . These silica NC (SiNC) coatings can increase hardness, wear resistance and fracture toughness with relatively low percentages of SiNPs incorporated into polymers . Polyacrylate‐based and other inorganic materials SiNCs exhibited improved electrical resistivity compared to traditional counterparts, resulting in a more energy efficient, organic light‐emitting devices .…”
Section: Introductionmentioning
confidence: 99%